Some properties of the model of a superconductor with pair hopping and magnetic interactions at half-filling - Kapcia, Konrad (Polish Academy of Sciences, Institute of Physics, al. Lotników 32-46, Pl-02-668 Warsaw, Poland, 2012)
We present our preliminary studies of an effective model of a superconductor with short coherence length involving magnetic interactions. The Hamiltonian considered consists of (i) the effective on-site interaction U, (ii) the intersite magnetic exchange interactions (Jz, Jxy) between nearest-neighbors and (iii) the intersite charge exchange term I, determining the hopping of electron pairs between nearest-neighbor sites. In the analysis of the phase diagrams and thermodynamic properties of this model for half-filling (n=1) we have adopted the variational approach, which treats the on-site interaction term exactly and the intersite interactions within the mean-field approximation. One finds that the system considered can exhibit very interesting multicritical behaviors (including tricritical, critical-end and bicritical points) caused by the competition between magnetism and superconductivity, even for n=1. Our investigations show that, depending on the values of interaction parameters, the system at half-filling can exhibit three homogeneous phases: superconducting (SS), (anti-)ferromagnetic (F) and nonordered (NO). The transitions between ordered phases (SS, F) and the NO phase can be first order as well as second order ones, whereas SS-F transition is first order one. Temperature dependencies of the order parameters and thermodynamic properties of the system at the sequence of transitions: SS-F-NO with increasing temperature for J/I=0.3, U/I0 = 0.69 and n=1 are also presented.
This is an author-created, un-copyedited version of an article accepted for publication in Acta Physica Polonica A. The Version of Record is available online at http://przyrbwn.icm.edu.pl/APP/PDF/121/a121z4p104.pdf
Keywords: magnetic orderings; superconductivity; extended Hubbard model; atomic limit; phase separation